Integrity over fidelity: transformational lessons from youth participatory action research to nurture SEL with adolescents - Meland, Emily Anne; Brion-Meisels, Gretchen (Frontiers in Psychology, 2023)
Much has been written about social and emotional learning (SEL) and its positive impact on young people’s academic and life outcomes, yet most of this research is based in early childhood and elementary settings. SEL programming for adolescents has shown mixed results, with many programs proving to be largely ineffective or even showing slightly negative impacts for some youth. Adherence to scripted SEL curricula, or “fidelity” to the program components, is often seen by young people to be “lame”, inauthentic, and condescending, failing to connect to the topics and issues that feel most critical to them in this stage of their development. For all students, and especially for those whose identities have been systematically marginalized or oppressed by the dominant culture, SEL programming that fails to explicitly address these experiences of injustice often feels inauthentic and out of touch for youth. Therefore, effective implementation of SEL for adolescents is likely to require skillful adaptation and responsiveness to the identities, interests, and motivations of students by educators. In this case, effective SEL may look less like fidelity to a specific set of scripts, sessions, or activities, but rather a commitment to the wholeness of a set of core principles, relationships, and opportunities for adolescent exploration and leadership/empowerment, or what we will call integrity of implementation. In this paper, we present one promising approach to adolescent social and emotional development – youth participatory action research (YPAR) – and the ways in which studying the YPAR process (in addition to the research topics selected by youth) can provide key insights into the social and emotional learning and development of youth.